New design paradigm for boundary and urban public spaces - Azimin Samsul Mohd Tazilan; Zuhairuse Md Darus; Abdul Halim Ismail; Azami Zaharin (2006)
Cities of today are shaped more by boundary rather than by rational design. Boundaries, on the other hand, are the result of the amalgamation of a community’s collective living experiences. Architecture defines boundary as a formal division of lines, walls and partitions. In public spaces, boundaries can be blurred arising from needs and usages. Conventional boundaries, because they do not take into account public and cultural needs, has resulted in unyielding spatial characteristics which stifle creativity in the utilization of space. In this paper, public space, in particular the streetscape will be examined in order to redefine the space usage. This paper also offers solutions in the use of street space in order to create a better quality of life